Future challenges of occupational safety and health policy-making in the UK - Leka, Stavroula; Jain, Aditya Kailash; Zwetsloot, Gerard I.J.M.; Andreou, Nicholas; Hollis, David (Taylor & Francis, 2016)
Understanding the changing landscape of occupational safety and health (OSH) regulation and standards and its implications are of central importance for ensuring that OSH outcomes are not compromised and the needs of different types of organizations are met. It is also important for developing appropriate strategies to anticipate and deal with future challenges for OSH policy-making. This paper draws on findings from two qualitative studies with key OSH stakeholders in the UK that were conducted as part of a research programme funded the Institution of Occupational Safety & Health. The aim of the first study was to elicit the views of key stakeholders on changes in the current OSH landscape so as to understand the nature and implications of these changes. The second study explored stakeholder perspectives on how to secure the optimal OSH landscape in the UK by addressing key future challenges for OSH policy-making.